Production of brown algae pyrolysis oils for liquid biofuels depending on the chemical pretreatment methods - Choi, Joonhyuk; Choi, Jae-Wook; Suh, Dong Jin; Ha, Jeong-Myeong; Hwang, Ji Won; Jung, Hyun Wook; Lee, Kwan-Young; Woo, Hee-Chul (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
Based on observations of rapidly growing biochar in fluidization beds, kelp (Saccharina japonica), a species of brown algae, was pretreated for the efficient operation of pyrolysis processes to produce pyrolysis oils. The removal of catalytically active inorganic minerals and the softening of polymeric seaweed structures were performed by means of chemical treatments, including a CaCl2 treatment to isolate valuable and sticky fucoidan and a sulfuric acid treatment to remove catalytically active minerals. The sulfuric acid pretreatment significantly reduced the inorganic elements but did not significantly affect the properties of the pyrolysis oil compared to the non-treated kelp pyrolysis oil. Whereas the non-treated kelp produced significantly large chunks of biochar, which hindered the continuous operation of pyrolysis, the kelp treated with sulfuric acid did not produce aggregated large particles of biochar, thereby offering a means of developing reliable continuous pyrolysis processes. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: MACROALGAE ENTEROMORPHA-PROLIFERA; BIO-OIL; HYDROTHERMAL LIQUEFACTION; MICROALGAE; SEAWEED; BIOMASS; LIGNIN; FUELS; TEMPERATURE; KINETICS